Metabolic Syndromes in Overweight/Obese School-Age Children - Lia Otiashvili MD (SAGE Publishing, 2022)
The research aimed at studying the phenomenological structure of metabolic syndromes in overweight and obese school-age children. The cohort of 210 students participated in the cross-sectional study. Among them 84 children (40%) were overweight/obese and 126 students (60%)-with normal weight. The incidence of abdominal obesity and arterial hypertension were studied and lipid profile was assessed in obese children. The results of research revealed the early manifestation of abdominal obesity (14.3%-16.7%), arterial hypertension (the elevation of systolic pressure-27.4%, the increase in diastolic pressure-10.7%) and hypercholesterolemia (9.5%) in the population of overweight/obese school age children, which allows to take prompt corrective actions on metabolic syndrome and reduce the risk of its formation.